Preclinical and first-in-human phase I clinical evaluation of Stampidine, a potent anti-HIV Pharmaceutical drug candidate - Cahn, Pedro; Rolon, Maria Jose; Gun, Ana Mirta; Ferrari, Ines; Dibirdik, Ilker; Qazi, Sanjive; Uckun, Fatih (My University, 2012)
The rationally designed novel anti-HIV drug candidate Stampidine exhibited (a) remarkable subnanomolar to low nanomolar in vitro ARV potency against genotypically and phenotypically NRTI-resistant primary clinical HIV isolates, non-nucleoside reverse transcriptase inhibitor (NNRTI)-resistant HIV-1 isolates, clinical non-B subtype HIV- 1 isolates (subtypes A, C, F, and G) originating from South America, Asia, and sub-Saharan Africa with resistance to stavudine, adefovir and tenofovir, as well as recombinant HIV clones containing common patterns of RT mutations responsible for NRTI resistance such as multiple TAMs plus M184V, multiple TAMs plus T69 insertion, and Q151 complex (b) favorable, safety profile in mice, rats, dogs, and cats, and (c) promising prophylactic in vivo anti-retroviral activity in Hu-PBL-SCID mice as well as therapeutic anti-retroviral activity in FIV-infected domestic cats. Notably, in a placebo-controlled Phase I study involving 30 therapy-naïve adult HIV-infected adult patients, formulated GMPgrade oral Stampidine capsules did not cause dose-limiting toxicity at single dose levels ranging from 5 to 25 mg/kg. Taken together, the presented favorable preclinical and early clinical safety/activity profile of Stampidine warrants its further development as a new anti-HIV drug candidate. © 2012 Cahn P, et al.